Preparation of organic-inorganic chitosan@silver/sepiolite composites with high synergistic antibacterial activity and stability. (1st December 2020) - Li, Dongdong; Gao, Xuan; Huang, Xuechun; Liu, Pingle; Xiong, Wei; Wu, Shengtao; Hao, Fang; Luo, He'an
Graphical abstract: Highlights: CTs@Ag/Sep was prepared by grafting of chitosan and silver on sepiolite. CTs is in favor to form well dispersed nano silver and improves antibacterial effect. CTs@Ag/Sep showed good inhibitory effect to S. aureus, E. coli and Aspergillus niger. CTs@Ag/Sep presented very low cytotoxicity to A549 cells. Abstract: Organic-inorganic antibacterial materials chitosan@silver/sepiolite (CTs@Ag/Sep) was prepared by grafting organometallic chelate of chitosan and silver on sepiolite. The prepared samples were characterized, and their antibacterial properties were detected. The carrier sepiolite was beneficial for the thermal stability of the composite material. The utilization of silver was enhanced and its amount of usage could be obviously reduced by introduction of nontoxic chitosan which was benefical for the formation of highly dispersed silver nanoparticles on the CTs@Ag/Sep by the interaction between the silver ion and the plentiful amino and hydroxyl groups on the chitosan, thus improved the antibacterial activities and stability. The average width of the inhibition zone of CTs@Ag/Sep against Staphylococcus aureus ( S. aureus ), Escherichia coli ( E. coli ) and Aspergillus niger were 51.8, 31.8, and 44.7 mm, respectively. The cytotoxicity of CTs@Ag/Sep was further evaluated with A549 cells, and the results indicated that it exhibited low cytotoxicity to eukaryotic cells.